New dimensions in regional integration - De Melo, Jaime ed. (Cambridge Univ. P. CambridgeGB, 1993)
Reviews the causes behind the rise of trading blocs and discusses the economics of trading blocs. Looks at whether the first wave of regionalism achieved its goals. Examines the 'new' regionalism and discusses the implications of this 'new' regionalism for countries with little bargaining power.